2019
DOI: 10.1259/dmfr.20180416
|View full text |Cite
|
Sign up to set email alerts
|

Correlation analysis between the SUVmax of FDG-PET/CT and clinicopathological characteristics in oral squamous cell carcinoma

Abstract: Objectives:  To investigate the relationship between maximum standardized uptake value (SUVmax) of 18F-FDG PET/CT and clinicopathological features of oral squamous cell carcinoma (OSCC), in order to formulate a better clinical guideline. Methods:  In 104 patients with OSCC confirmed by pathology, there were 67 males and 37 females (age, 33–76 years; mean age, 56 years).18FDG, 18-fludeoxyglucose (18F-FDG) PET/CT manifestations and the clinicopathological features of the 104 patients were retrospectively analyse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 15 publications
1
5
0
Order By: Relevance
“…Correlation analysis demonstrated significant association between SUVmax and grading as well as UICC. These results indicate a dependency between the local metabolic activity of tumors as seen by PET-CT and histopathological characteristics of the tumor, which are consistent with previous results [35]. According to Stalder et al [52], we also found a strong relationship between SUVmax and the presence of bone infiltration in our study collective [52].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Correlation analysis demonstrated significant association between SUVmax and grading as well as UICC. These results indicate a dependency between the local metabolic activity of tumors as seen by PET-CT and histopathological characteristics of the tumor, which are consistent with previous results [35]. According to Stalder et al [52], we also found a strong relationship between SUVmax and the presence of bone infiltration in our study collective [52].…”
Section: Discussionsupporting
confidence: 93%
“…Studies on different tumor entities confirmed the feasibility to assign a predictive value to this metabolic activity quantified by the SUVmax, measured in 18 [F]FDG PET and PET-CT. The method has shown to represent a valid marker for prognosis, recurrence and survival time [ 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 ]. Berghmans et al also highlighted this connection early in their review of the predictive value of SUVmax on survival times in patients with non-small-cell lung cancer (NSCLC) and identified a survival-dependent threshold for SUVmax [ 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…Although Leifels et al ( 3 ) did not observe significant differences in SUV max between various T and N stages, Nakajo et al ( 16 ) reported significantly higher SUV max values in T3 and T4 tumors. In a previous study, T4 tumors had significantly higher SUV max values than T1-3 tumors in patients with oral squamous cell carcinoma ( 27 ). In our study, we observed higher MTV (40% threshold) values in T4 tumors than T1-3 tumors.…”
Section: Discussionmentioning
confidence: 84%
“…Choi et al ( 34 ) and Nakajo et al ( 16 ) also found no association between SUV max and ADC with grade. Zheng et al ( 27 ) analyzed 104 patients with oral SCC and observed an association between SUV max and poor differentiation. Different grading systems in HNSCC include parameters such as lymphoplasmacytic infiltration, keratinization degree of the tumor, nuclear and cellular polymorphism, and invasion pattern ( 35 ).…”
Section: Discussionmentioning
confidence: 99%
“…As one of the important parameters of 18 F-FDG PET/CT, the SUVmax is able to measure the activity of tissue metabolism, which is strongly correlated with cell division and proliferation (49). Thus, the SUVmax is considered to sensitively predict the biological behavior of tumors that is influenced by various clinical factors (50).…”
Section: Discussionmentioning
confidence: 99%